Dynamic Splitting Experimental Study on Sandstone at Actual High Temperatures under Different Loading Rates - Qi Ping; Mingjing Wu; Pu Yuan; Haipeng Su; Huan Zhang (Shock and Vibration)
The tensile failure of rocks is a common failure mode in rock engineering. Many studies have been conducted on the tensile strength and failure mode of rocks after high-temperature treatment under dynamic loading. However, research on the effects of high temperature on the dynamic splitting tensile characteristics of sandstone at actual high temperatures is lacking. To investigate the dynamic tensile characteristics of rocks at actual high temperatures, split Hopkinson pressure bar (SHPB) test apparatus and high-temperature environment box were used to perform dynamic splitting tensile tests under six striker velocities for sandstone specimens at 25°C–800°C. The dynamic splitting tensile strength, radial strain, average strain rate, and failure mode of sandstone under different test conditions were investigated. Test results revealed that the brittleness of sandstone specimens is enhanced at 200°C and 400°C, but slight ductility is observed at 600°C and 800°C. The strain rate effect of dynamic tensile strength is closely related to temperature. When the striker velocity exceeds 2.3 m/s, the dynamic radial strain first decreases and then increases with rising temperature. A quadratic polynomial relationship between the dynamic radial strain and temperature was observed. The temperature effect on the average strain rate is strong at low striker velocity and weak at high striker velocity. In the dynamic splitting tensile tests, high-temperature sandstone specimens are split into two semicylinders along the radial loading direction.